MOOCs : design, use and business models - Pomerol, Jean-Charles; Epelboin, Yves; Thoury, Claire (London, UK : ISTE Ltd ; Hoboken, NJ : John Wiley and Sons, Inc., 2015)
MOOCs (Massive Online Open Courses) are shaking up the traditional forms of primary and continuing education and training. These new distance teaching tools which take advantage of the Web and social network revolution are making us think again about how we teach and learn. However, for all that, do they constitute a threat to universities and schools, or are they just a new tool to change the traditional classroom? This book brings together answers to the questions most often posed: Is the MOOC really new or is it just a modern form of distance education? What is a MOOC, how does it d.
5.2. MOOCs and lifelong learning5.2.1. At present, which are the largest groups of MOOC users?; 5.2.2. Various uses for MOOCs; 6: Conclusions: What Does the Future Hold for MOOCs?; 6.1. "To MOOC or not to MOOC"?; 6.2. Why and for whom should MOOCs be developed?; 6.3. What can be done to support the development of MOOCs?; 6.3.1. Hardware and software platforms; 6.3.2. Encouragement of developers; 6.4. What can be done to support the users of MOOCs?; 6.5. A step towards digital learning houses (DLHs); Bibliography; Glossary of Terms; Index.
Includes bibliographical references and index.
Vendor-supplied metadata.
Keywords: MOOCs (Web-based instruction); Distance education; Education, Higher -- Computer-assisted instruction; MOOCs (Web-based instruction); Open learning; EDUCATION -- Administration -- General; EDUCATION -- Organizations & Institutions; MOOCs (Web-based instruction); Electronic books; Electronic books